The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1143/jjap.48.06fh12
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Nanoimprint of a Polystyrene and Poly(4-vinylpyridine) Double-Layer Thin Film and Visualization Determination of Its Internal Structure by Transmission Electron Microscopy

Abstract: In this research, we studied the morphological transformation of a poly(4-vinylpyridine), P4VP, thin film on a polyimide substrate after thermal nanoimprint and investigated its effect on electron beam (EB) exposure by atomic force microscopy. On the basis of the results, we designed a patterned double-layer thin film consisting of polystyrene, PSt, as the outermost inactive layer and P4VP as the underlying active layer for Cu electroless deposition. We studied how to prepare and confirm the integrity of a dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…31) We previously reported that thin film surfaces of PS and poly(4-vinylpyridine) could be transformed by thermal nanoimprinting at 80 °C which was lower than glass transition temperatures of 92 °C for bulk PS and 137 °C for bulk poly(4-vinylpyridiene). 45) The depth of transformed film surface was increased with an increase in molding temperature under a constant applied pressure. This suggests that polymers in a region from the outermost surface to the film inside showed a lowered glass transition temperature.…”
Section: Segregation Of Al Component In Sis-treated Zep520a Filmsmentioning
confidence: 98%
“…31) We previously reported that thin film surfaces of PS and poly(4-vinylpyridine) could be transformed by thermal nanoimprinting at 80 °C which was lower than glass transition temperatures of 92 °C for bulk PS and 137 °C for bulk poly(4-vinylpyridiene). 45) The depth of transformed film surface was increased with an increase in molding temperature under a constant applied pressure. This suggests that polymers in a region from the outermost surface to the film inside showed a lowered glass transition temperature.…”
Section: Segregation Of Al Component In Sis-treated Zep520a Filmsmentioning
confidence: 98%
“…TNIL was performed at 150 °C and a pressure of 20 MPa for 5 min using a nanoimprint system (Meisho Nanoimprinter NM-400). 24,25) Then, the mold was removed at 60 °C. The residual layer was removed by O 2 plasma using a reactive ion etching (RIE) system (Samco RIE-1).…”
mentioning
confidence: 99%